'Surprisingly little evidence' on how best to treat actinic keratosis in organ transplant recipients. (2nd January 2019) - Werner, R.N.; Nast, A.
Abstract : Linked Article: Heppt et al. Br J Dermatol 2019;180 :43–50 .